Teachers' Perception of Digitization of Mathematics Learning at Madrasah Aliyah Muhammadiyah Watulimo Trenggalek - Luthfi Widodo; Rahyu Setiani; Ajar Dirgantoro (JURNAL PENDIDIKAN MATEMATIKA, 2025)
Digitization of learning as a form of innovation requires adaptation and acceptance from teachers. Teacher perception is a key factor in determining the success of this innovation's implementation in schools. This study aims to describe the implementation of digitization in mathematics learning and teachers' perceptions of digitization in learning at Madrasah Aliyah Muhammadiyah (MAM) Watulimo Trenggalek. This study uses a descriptive qualitative approach. Data were collected through interviews, observations, and documentation, and tested for validity through triangulation. The results of the study show that the digitization of mathematics learning at MAM Watulimo has been applied comprehensively across the planning, implementation, and evaluation stages of learning. The number of classes supports this implementation in line with standards, the availability of digital devices, adequate madrasah facilities, and teacher collaboration. Teachers' perceptions of the digitization of mathematics learning are generally positive. Teachers assessed that this innovation offers relative advantages, such as increased efficiency, easier access to materials, and a variety of learning methods. In terms of compatibility, teachers feel that digitalization aligns with professional values and the needs of today's students. However, there is still a negative perception of the complexity, especially regarding the constraints of using technology by teachers who are not familiar with digital devices.Keywords: Digitalization, Mathematics Learning, Teacher Perception